2008
DOI: 10.1517/14656560802560237
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for esophageal cancer

Abstract: There is considerable controversy over the level of evidence from randomized trials underpinning management decisions for patients presenting with localized cancer of the esophagus and esophago-gastric junction. There is also an optimism that new drugs and new approaches, including response prediction based on sequential 18 FDG-PET scanning following induction chemotherapy, may improve treatments pathways and outcomes. In this review we assess the level of evidence from the major published trials, and discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…A 30-year-old woman with a carcinoma of the tongue and undiagnosed Fanconi anemia developed severe mucositis following radiotherapy (Alter et al 2005). Presently, chemotherapy and radiotherapy are the main remedies for treating or down-staging of ESCC patients before surgery with occasional severe side effects (Alter et al 2005;Murphy et al 2008), and it is important to evaluate if their similar toxicities are observed in ESCC patients with variants in the FA genes who are treated with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…A 30-year-old woman with a carcinoma of the tongue and undiagnosed Fanconi anemia developed severe mucositis following radiotherapy (Alter et al 2005). Presently, chemotherapy and radiotherapy are the main remedies for treating or down-staging of ESCC patients before surgery with occasional severe side effects (Alter et al 2005;Murphy et al 2008), and it is important to evaluate if their similar toxicities are observed in ESCC patients with variants in the FA genes who are treated with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been a dramatic epidemiological shift in the incidence of esophageal adenocarcinoma (EAC), with rates rising by 600% over the last 30 years in Western populations (1 3 Christian N Paxton, 4 Katherine Geiersbach, 4,5 Mary P Bronner, 4,5 Jacintha O'Sullivan, 1 John V Reynolds, 1 and Stephen G Maher Esophageal adenocarcinoma (EAC) has a poor prognosis and is increasing in incidence in many Western populations. Neoadjuvant chemoradiation therapy (CRT) followed by surgery is increasingly the standard of care for locally advanced EAC; however, resistance to treatment is a significant clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…chemoradiation therapy (CRT) followed by surgery increasingly becoming the standard of care in Ireland, North America and several European centers (4).…”
mentioning
confidence: 99%
“…Oof the two main histological types – adenocarcinoma (AC) and squamous cell carcinoma (ESCC) – the latter is still the most prevalent one in developing countries . Single modality treatments, multimodal treatments, and palliative treatments are established methods for disease management .…”
mentioning
confidence: 99%